Technical features of the Islamic and Chinese ceramics (Al-Academy, 2016)
Eat this research study features Technical Ceramics Islamic and Chinese The study of four chapters , such as the first chapter the general framework for research and containing the problem that put the following question: Mamdy effect features art on porcelain Islamic and Chinese ) , and whether there are dimensions of the aesthetic , intellectual and ideological in porcelain Islamic and Chinese with lies the importance of research in the promise of a qualitative study and add a scientific theme features art in porcelain Islamic and China , and the objectives of this study One was in the detection of features technical Ceramics Islamic and Chinese study examined the length of time the ninth century AD , and the tenth century AD , and in the field of ceramics, specifically the dishes and spatially ( Iraq , China ) , also known researcher terminology contained in the search . The researcher then moved to the second quarter , which included a theoretical framework and previous studies , which included three sections , taking the first study attribute the concept of art in porcelain . The second section has focused on the study of 1. Influence of religious thought on porcelain Islamic 2. Historical context of Ceramics Islamic Abbasid era , while the third section is the study of thought, and legends in Chinese porcelain 2. Historical context of the china and the end including resulting theoretical framework and previous studies where salvation indicators formed a total regarding aspects of search to detect The third chapter is devoted to research and determine the procedures society and appointed according to an objective basis , samples were selected and analyzed within the descriptive approach ( analytical ) , have been dealt with (4) samples to be discussed to reveal the functional and technical features and aesthetic . This study concluded displays the most important findings contained in Chapter IV and out most important Amatrah of the findings and conclusions and finally put the researcher some recommendations and suggestions for other researchers and related research sources